Comparison between irrigation and conventional treatment for empyema and pneumonectomy space infection. Issue 4 (April 1981) - Rosenfeldt, F L; McGibney, D; Braimbridge, M V; Watson, D A
Abstract : A new method of treating pleural empyema or pneumonectomy space infection by irrigation was evaluated in 11 patients. The infected cavities were filled with an antibiotic or antiseptic solution for three hours, and allowed to drain for one hour. This cycle was repeated every four hours for seven to 10 days. When cultures of the infected cavity became sterile the irrigation tube was removed and the wound sealed. Using this method, infection was eradicated after an average of 11 days in five of six patients with pleural empyema and in all five patients treated for an infected pneumonectomy space, including one with a bronchopleural fistula. The results of treating 58 similar cases of intrapleural sepsis over a 10-year period by the standard methods of aspiration, open drainage, decortication, or thoracoplasty were compared with the results of irrigation. In general, cyclical irrigation resulted in a shorter hospital stay and a shorter period of wound drainage than other methods.